Evaluation of uterine brachytherapy as primary treatment option for elderly patients with medically inoperable endometrial cancer: a single-center experience and review of the literature - Arians, Nathalie; Oelmann-Avendano, Jan Tobias; Schmitt, Daniela; Meixner, Eva; Wark, Antje; Hörner-Rieber, Juliane; El-Shafie, Rami; Uzun-Lang, Kristin; Wallwiener, Markus; Debus, Jürgen (Cancers, 2020)
We aimed to gain more evidence regarding the feasibility, toxicity, and oncological outcome of primary brachytherapy in patients with medically inoperable endometrial cancer. Thirteen patients receiving primary brachytherapy ± external beam radiotherapy (EBRT) for endometrial cancer due to medical inoperability were identified. The Kaplan–Meier method was used to estimate overall survival (OS), progression-free survival (PFS), and local failure-free survival (LFFS). Univariate outcome analyses were performed using the log-rank test. Peri-interventional complications, acute and chronic toxicities were evaluated. Additionally, we performed a Pubmed search and review of the literature of the last 10 years. Mean age at time of diagnosis was 73.9 years (60.4–87.1 years). Eleven patients were staged FIGO IA/B and one patient each with FIGO IIIA and IIIC. Kaplan–Meier-estimated 2-/5-year LFFS were 76.2%/56.4%, respectively. High grading correlated with a worse LFFS (p = 0.069). Kaplan–Meier-estimated 2-/5-year PFS were 76.9%/53.8% and 2-/5-year-OS were 76.9%/69.2%, respectively. No acute toxicities > grade II and only two late toxicities grade II/III occurred. We observed three peri-interventional complications. The available evidence suggests high rates of local control after definitive brachytherapy for inoperable endometrial cancer with a favorable toxicity profile. Definitive brachytherapy +/− EBRT should be considered as the preferred approach for this patient group.
Gesehen am 03.12.2020